T-cell activation or tolerization: the Yin and Yang of bacterial superantigens - Sähr, Aline; Förmer, Sandra; Hildebrand, Dagmar; Heeg, Klaus (Frontiers in Microbiology, 2015)
Bacterial superantigens are exotoxins from pathogens which interact with innate and adaptive immune cells. The paradox that superantigens cause activation and inactivation/anergy of T-cells was soon recognized. The structural and molecular events following superantigen binding to antigen presenting cells (APCs) followed by crosslinking of T-cell receptors were characterized in detail. Activation, cytokine burst and T-cell anergy have been described in vitro and in vivo. Later it became clear that superantigen-induced T-cell anergy is in part caused by superantigen-dependent activation of T-regulatory cells (Tregs). Although the main focus of analyses was laid on T-cells, it was also shown that superantigen binding to MHC class II molecules on APCs induces a signal, which leads to activation and secretion of pro-inflammatory cytokines. Accordingly APCs are mandatory for T-cell activation. So far it is not known, whether antigen presenting cells play a role during superantigen-triggered activation of Tregs. We therefore tested whether in superantigen (Streptococcal pyrogenic exotoxin A) -treated APCs an-anti-inflammatory program is triggered in addition. We show here that not only the anti-inflammatory cytokine IL-10 and the co-inhibitory surface molecule PD-L1 (CD274) but also inhibitory effector systems like indoleamine 2,3-dioxygenase (IDO) or intracellular negative feedback loops (suppressor of cytokine signaling molecules, SOCS) are induced by superantigens. Moreover, cyclosporine A completely prevented induction of this program. We therefore propose that APCs triggered by superantigens play a key role in T-cell activation as well as inactivation and induction of Treg cells.